Kergueleniidae fam. nov. (Crustacea: Amphipoda: Lysianassoidea) in Australian waters - Lowry, J. K.; Stoddart, H. E. (Zootaxa, 2010)
The new lysianassoid amphipod family Kergueleniidae is established and the genera Clepidecrella and Kerguelenia are reported from Australian waters for the first time. Nine new species are described: Clepidecrella abeona sp. nov., C. cataraqui sp. nov., C. colliboi sp. nov., C. ira sp. nov., Kerguelenia euroka sp. nov., K. kanowna sp. nov., K. kawatiri sp. nov., K. leura sp. nov. and K. matilda sp. nov. Keys are given to all species of each genus.